2012
DOI: 10.2138/am.2012.4178
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-layered structure formation during trans-vacant Al-rich illite partial dehydroxylation

Abstract: The <1 µm fraction of a trans-vacant 1M illite (RM30) was studied by conventional and synchrotron X-ray diffraction (XRD) techniques, combined with thermogravimetric (TG, DTG) methods to investigate the structural transformation of illite at different temperatures and degrees of dehydroxylation (D T ). The oriented specimens preheated at 300 and 680 °C correspond to the non-dehydroxylated (D T = 0) and completely dehydroxylated (D T = 100%) 1 M illite structures. Deviation of the basal reflection positions fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This conclusion agrees with the results obtained by Bergaya et al (1996), who studied the ‘Gabriel’ (UK) kaolinite sample by transmission electron microscopy and selected area electron diffraction using controlled-rate thermal analysis and concluded that only two phases – initial non-dehydroxylated kaolinite and metakaolinite – coexist during the sample dehydroxylation. Such coexistence probably means that the dehydroxylation process occurs as a zero-order reaction, which is also typical of partially dehydroxylated dioctahedral 2:1 layer silicates including clay minerals (Drits et al , 2011a, 2011b, 2012a, 2012b). This implies that, during partial dehydroxylation, a non-dehydroxylated layer transforms into a completely dehydroxylated layer without the formation of any intermediate structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This conclusion agrees with the results obtained by Bergaya et al (1996), who studied the ‘Gabriel’ (UK) kaolinite sample by transmission electron microscopy and selected area electron diffraction using controlled-rate thermal analysis and concluded that only two phases – initial non-dehydroxylated kaolinite and metakaolinite – coexist during the sample dehydroxylation. Such coexistence probably means that the dehydroxylation process occurs as a zero-order reaction, which is also typical of partially dehydroxylated dioctahedral 2:1 layer silicates including clay minerals (Drits et al , 2011a, 2011b, 2012a, 2012b). This implies that, during partial dehydroxylation, a non-dehydroxylated layer transforms into a completely dehydroxylated layer without the formation of any intermediate structure.…”
Section: Discussionmentioning
confidence: 99%
“…• At each stage of partial dehydroxylation, the heated specimens consist of two phases: initial non-dehydroxylated kaolinite and metakaolinite. • The direct transformation of non-dehydroxylated kaolinite crystallites into metakaolinite means that the process corresponds to a zero-order reaction (Drits et al, 2011a(Drits et al, , 2011b(Drits et al, , 2012a(Drits et al, , 2012bDrits & Derkowski, 2015), according to which non-dehydroxylated kaolinite crystallites transform into hydroxylated metakaolinite. • The XRD pattern of metakaolinite and thus its structure remain the same regardless of the degree of partial dehydroxylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8), from 400 to 850 ˚C for chlorites (Lempart et al, 2018) and from 750 to 1100 ˚C for talc (Zhang et al, 2006). This process consists of a reaction between hydroxyl groups (OH) forming water molecules (Drits et al, 1995;Drits et al, 2012a;Drits et al, 2012b;Guggenheim et al, 1987;Vedder and Wilkins, 1969):…”
Section: Reduction Of H 2 O By Fe(ii) Oxidationmentioning
confidence: 99%